2017
DOI: 10.1002/ijc.31031
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic position, population density and site‐specific cancer mortality: A multilevel analysis of Belgian adults, 2001–2011

Abstract: Our study explores the association between individual and neighborhood socioeconomic position (SEP) and all-cancer and site-specific cancer mortality. Data on all Belgian residents are retrieved from a population-based dataset constructed from the 2001 census linked to register data on emigration and mortality for [2001][2002][2003][2004][2005][2006][2007][2008][2009][2010][2011]. The study population contains all men and women aged 40 years or older during follow-up. Individual SEP is measured using education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 60 publications
(129 reference statements)
4
32
0
1
Order By: Relevance
“…Previous studies investigating the influence of social environment on cancer survival for several solid tumor sites with comparable methodology (i.e. population‐based registries data, ecological deprivation index, net survival) also showed lower survival among patients living in the most deprived environments compared to those living in the least deprived ones, for most cancer sites . More broadly, all studies investigating social inequalities in cancer survival worldwide have reported lower survival among the most deprived for a large majority of cancer sites, with no significant inverse association .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous studies investigating the influence of social environment on cancer survival for several solid tumor sites with comparable methodology (i.e. population‐based registries data, ecological deprivation index, net survival) also showed lower survival among patients living in the most deprived environments compared to those living in the least deprived ones, for most cancer sites . More broadly, all studies investigating social inequalities in cancer survival worldwide have reported lower survival among the most deprived for a large majority of cancer sites, with no significant inverse association .…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, we used a validated indicator for social deprivation, developed and used in several European countries . The EDI offers an acceptable approximation of social deprivation at the individual level when used in small geographic units such as IRIS, while also providing information on the social environment, known to have a proper effect on cancer survival for some cancer sites . The measure of the variation of survival between the least and the most deprived quintiles brought new information on the extent of survival disparities according to social deprivation that can be compared across cancer sites or different times of follow‐up since it is a relative measure of the deprivation gap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer is a major health issue, which is ranked as a leading cause of mortality worldwide [1,2]. To treat cancer, chemotherapy is one of the most commonly used therapeutic methods as it is the most effective approach [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the 1970s, Western scholars began to pay attention to the suburbanization of the urban population. The research focused mainly on the changes in population distribution [9,10], the relationship between population density changes and social phenomena [11][12][13], population suburbanization and spatial structure [14,15] and so on.…”
Section: Introductionmentioning
confidence: 99%